Annual bullion review : 1961-67 - Montagu (Samuel) and Company, ltd. [from old catalog] (Samuel Montagu & Co, 1962., 1962)
It contains six issues of the review from 1961-1967 and it examines the London Gold Market in years covered and the problems of contending with other currencies like the U.S dollar.
usc 14/02/2019
Ref.
Keywords: Gold; Silver; Platinum; Money; Currency question; Precious metals--Prices; Great Britain